Ag2CO3-catalyzed cycloaddition of organic azides onto terminal alkynes: A green and sustainable protocol accelerated by aqueous micelles of CPyCl. Issue 16 (18th April 2019) - Sultana, Jasmin; Khupse, Nageshwar D.; Chakrabarti, Srijita; Chattopadhyay, Pronobesh; Sarma, Diganta
Graphical abstract: Highlights: Simplest Cu-free protocol for azide-alkyne cycloaddition reaction reported so far. Non toxic cationic surfactant, CPyCl speeded up the reaction. Negligible E-factor as compared to literature reports. Wide substrate scope with good to excellent yields. Abstract: Using catalytic amount of Ag2 CO3 a simple, efficient and copper free green protocol has been developed to synthesize 1, 4-disubstituted 1, 2, 3-triazoles regioselectively. Here, the cationic surfactant, cetylpyridinium chloride (CPyCl) in water provides a micellar media and accelerates the subsequent Ag(I)-catalysed azide-alkyne cycloaddition (AgAAC) reaction by increasing the concentration of reactants in the micellar pseudophase. Our method is found to be environmentally friendly from E-factor measurement. The surfactant, CPyCl is found to be nontoxic .